Restructuring the state: mainstream responses to regional nationalism - Toubeau, Simon (Oxford University Press, 2017)
Under what conditions are ‘holding-together’ federations created? And what shapes the development of their territorial structures? This article answers these questions through a comparative-historical analysis of territorial restructuring in Belgium, Spain and the UK. It shows that ‘holding-together’ federations are created during a critical juncture opened by a surge of regional nationalism and that the strategic responses of mainstream parties to this threat are conditioned by their ideology. These constitutional settlements put countries on a path of institutional development that is conditioned by mainstream parties’ ideational adaptation to the political foundations of the federation and by their power in the system of inter-governmental relations. Even when regionalist parties regain control of the agenda, mainstream parties’ ideological adherence to the norms enshrined in the constitutions, coupled with their resilient power in the system of inter-governmental relations, means that institutional change is gradual. These insights bear relevance for institutional theory and for comparative federalism.